Anthropometric and training variables related to half-marathon running performance in recreational female runners - Knechtle, B.; Knechtle, P.; Barandun, U.; Rosemann, T. (The Physician and Sportsmedicine, 2011)
The relationship between skin-fold thickness and running has been investigated in distances ranging from 100 m to the marathon distance (42.195 km), with the exclusion of the half-marathon distance (21.0975 km). We investigated the association between anthropometric variables, prerace experience, and training variables with race time in 42 recreational, nonprofessional, female half-marathon runners using bi- and multivariate analysis. Body weight (r, 0.60); body mass index (r, 0.48); body fat percentage (r, 0.56); pectoral (r, 0.61), mid-axilla (r, 0.69), triceps (r, 0.49), subscapular (r, 0.61), abdominal (r, 0.59), suprailiac (r, 0.55), and medial calf (r, 0.53) skin-fold thickness; mean speed of the training sessions (r, -0.68); and personal best time in a half-marathon (r, 0.69) correlated with race time after bivariate analysis. Body weight (P = 0.0054), pectoral skin-fold thickness (P = 0.0068), and mean speed of the training sessions (P = 0.0041) remained significant after multivariate analysis. Mean running speed during training was related to mid-axilla (r, -0.31), subscapular (r, -0.38), abdominal (r, -0.44), and suprailiac (r, -0.41) skin-fold thickness, the sum of 8 skin-fold thicknesses (r, -0.36); and percent body fat (r, -0.31). It was determined that variables of both anthropometry and training were related to half-marathon race time, and that skin-fold thicknesses were associated with running speed during training. For practical applications, high running speed during training (as opposed to extensive training) may both reduce upper-body skin-fold thicknesses and improve race performance in recreational female half-marathon runners.